A new optimal controller designed for HVDC system - Albostan, A; Gökbulut, M (Taylor & Francis Ltd, 1999)
An adaptive optimal control strategy fbr two terminal HVDC systems embedded in an AC network is presented. The control is based upon real-time measurements performed on the AC/DC system. The system modelling is general and applicable to large-scale power systems with an embedded HVDC link. The control algorithm incorporates the nonlinear power system dynamic equations. A novel Feature of this development is the use of real-time system measurements as inputs to the optimal controller. The closed-loop optimal control law consists of both model- and measurement-based terms. The effectiveness of the optimal control algorithm in damping the electromechanical oscillations is illustrated with the use of a nine-bus AC/DC system.